2015
DOI: 10.1890/14-0469.1
|View full text |Cite
|
Sign up to set email alerts
|

Taking animal tracking to new depths: synthesizing horizontal–vertical movement relationships for four marine predators

Abstract: Abstract. In animal ecology, a question of key interest for aquatic species is how changes in movement behavior are related in the horizontal and vertical dimensions when individuals forage. Alternative theoretical models and inconsistent empirical findings mean that this question remains unresolved. Here we tested expectations by incorporating the vertical dimension (dive information) when predicting switching between movement states (''resident'' or ''directed'') within a state-space model. We integrated tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 61 publications
(74 reference statements)
1
103
1
Order By: Relevance
“…Swimming and diving are energetically costly; thus, air-breathing marine species are central-place foragers, where they must locate and capture prey in a 3-dimensional environment while returning back to the surface to meet their oxygen demands (Bestley et al 2015). At all locations, the variation of dive depth for ringed seals was lower when resident than when traveling, suggesting the active pursuit and handling of prey at particular depths.…”
Section: Resident Behaviour and Divingmentioning
confidence: 97%
“…Swimming and diving are energetically costly; thus, air-breathing marine species are central-place foragers, where they must locate and capture prey in a 3-dimensional environment while returning back to the surface to meet their oxygen demands (Bestley et al 2015). At all locations, the variation of dive depth for ringed seals was lower when resident than when traveling, suggesting the active pursuit and handling of prey at particular depths.…”
Section: Resident Behaviour and Divingmentioning
confidence: 97%
“…2010) and more complex state‐space models have started to integrate one‐dimensional diving traces with two‐dimensional horizontal movement tracks (Bestley et al. 2015), highlighting the importance and the difficulty of combining multiple dimensions and variables when animals move and forage in more than two dimensions. Here, we have demonstrated that unsupervised learning algorithms can provide an important additional tool for analysing accelerometer data.…”
Section: Discussionmentioning
confidence: 99%
“…However, rarely do these approaches account for the full suite of data available through modern satellite telemetry devices (Bestley et al , 2015. A common approach for discerning different behavioral states from satellite telemetry data is to use a switching state-space model (SSSM; Jonsen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…SSSM identifies a switch between two behaviors: transiting, which is characterized by movement at high rate and low turn angle; and area restricted search, which is characterized by localized movement of low rate and high turn angle (Bailey et al 2009). However, using SSSM based on horizontal metrics alone is not universally applicable to all species, as some species may forage while exhibiting wandering movements (Hays et al 2006), and residential movements do not always correspond to foraging (Bestley et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation